Anticariogenic Potential of Tabernaemontana Divaricata - Mini K. John; David Z. Cheriyan (Indian Journal of Dental Research)
Context: Many parts of Tabernaemontana divaricata (T. divaricata) including its leaf is used for the analgesic and antibacterial purpose by Adivasis of Kerala. Aims: To evaluate the antibacterial potential of T. divaricata against common caries pathogens like S. mutans and L. acidophilus. Settings and Design: Research is done in Biogenix Research Lab, Thiruvananthapuram. Methods and Material: Ethyl alcoholic extract of T. divaricata leaves is tested for its antibacterial action against common caries pathogens at various levels. It includes assessing the leaves’ antibacterial activity, acid production of bacteria in the presence of the study sample, Minimum inhibitory concentration (MIC), minimum bacterial concentration (MBC) and colony forming units (CFU) levels in the presence of the leaf extract. Statistical Analysis Used: In descriptive statistics, mean and standard deviation is used. Mann–Whitney U test, Independent Students T-test, Student Paired T-test, and One-way ANOVA followed by Turkeys Post hoc analysis are the tests used in inferential statistics. Results: It is found that T. divaricata has substantial antibacterial action against S. mutans and L. acidophilus. Conclusions: Our indigenous plants have a lot of medicinal properties. T. divaricata is no exception to this, though it is commonly considered as a garden plant. In the current study, it has been proven that its leaves have antibacterial action against oral pathogens. So, the research has to be taken to a further level for its medicinal application.